Role of Cell Cycles Phases and Pronuclei Morphology in Viability of Native and Cryopreserved Zygotes - Petrushko, M. P. (Problems of Cryobiology and Cryomedicine, 2005)
The cryopreservation results of human embryos being at zygote stage are presented. There was studied the effect of pronuclei morphology on zygote survival after freeze-thawing. The role of cell cycle phases in the zygote cryopreservation efficiency was found.